Cover Feature: Building a Cocrystal by Using Supramolecular Synthons for Pressure‐Accelerated Heteromolecular Azide–Alkyne Cycloaddition (Chem. Eur. J. 29/2019). Issue 29 (15th April 2019) - Meng, Xiao; Chen, Changqing; Deng, Xinyuan; Wang, Zhangyuan; Chen, Qi; Ma, Yuguo
Abstract : In a cocrystal, the azide–alkyne cycloaddition reaction between two different molecules was achieved, facilitated by the supramolecular synthons of carboxylic acids and amides through cooperative H‐bonding and arene–perfluoroarene interactions. The reaction was accelerated by pressure using a common hydraulic press to yield 1, 4‐triazole products with excellent regioselectivity. As demonstrated by the absence of side decarboxylation reactions in the products in the solid state, this strategy can provide a green synthetic route for products not directly accessible by traditional syntheses in solution. More information can be found in the Full Paper by Y. Ma et al. on page 7142 .